2017
DOI: 10.11591/ijpeds.v8.i4.pp1804-1813
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Frequency Transform Based Fault Detectionand Classificationof STATCOM Integrated Single Circuit Transmission Line

Abstract: <p align="center"> </p><p align="center"> </p><table width="593" border="1" cellspacing="0" cellpadding="0"><tbody><tr><td valign="top" width="387"><p>This paper discusses the time-frequency transform based fault detection and classification of STATCOM (Static synchronous compensator) integrated single circuit transmission line. Here, fast-discrete S-Transform (FDST) based time-frequency transformation is proposed for evaluation of fault detection and class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The imbalance in a category refers to the imbalance in the sample size of a category and its subcategories, or the data of a category has multiple different terms that are not so important, as shown in Figures 1(c) and 1(d). A large number of studies have shown that the imbalance of data between categories is not the only factor affecting classification learning, and the imbalance of data within categories is a key factor affecting the effect of classification [21]. Therefore, the classification problem of unbalanced data is mainly due to the complexity of the data distribution, as shown in Figures 1(b) and 1(c) (data overlap) and Figure 1(d) (small fragmentation problem); all of these problems will directly affect the classifier's learning result.…”
Section: Components Of An Integrated Classification Algorithm Formentioning
confidence: 99%
“…The imbalance in a category refers to the imbalance in the sample size of a category and its subcategories, or the data of a category has multiple different terms that are not so important, as shown in Figures 1(c) and 1(d). A large number of studies have shown that the imbalance of data between categories is not the only factor affecting classification learning, and the imbalance of data within categories is a key factor affecting the effect of classification [21]. Therefore, the classification problem of unbalanced data is mainly due to the complexity of the data distribution, as shown in Figures 1(b) and 1(c) (data overlap) and Figure 1(d) (small fragmentation problem); all of these problems will directly affect the classifier's learning result.…”
Section: Components Of An Integrated Classification Algorithm Formentioning
confidence: 99%